The Use of Social Media to Promote Societal Values in an Age of Corporate Competition: One Publishing Company’s Paradigm—Sage - Levenson, Harvey R. (Advances in Social Sciences Research Journal, 2024)
This is a paper on the use of social media postings by a publishing company focusing on issues of humane qualities of a diverse society, Sage. It is presented at a time when the value and control of social media is in question and being scrutinized by groups ranging from social scientists to the U.S. Congress as a medium that is sometimes considered more detrimental than good for users across demographics. However, Sage, part of a global academic community, developed uniquely positive messaging for social media and is a model for other organizations. Starting with a background of Sage, this study is deductive, starting with a brief history of publishing in the United States and the world, and continuing with the history of social media, with a focus on LinkedIn. The results present a model that is an anomaly for social media postings typical of companies messaging to its followers. Sage’s communication approach is not to sell products and services via social media, but to educate its followers and stakeholders on the important issues of the day, particularly those related to the social sciences. It “talks” to its followers and provides free advice on how to best address human needs across demographics, and the role that publishing plays in this. The research methods used in this study are Historical and Descriptive Research, Content Analysis, and Elite and Specialized Interviewing. The result is a model for communication via social media for organizations wanting to communicate effectively to its publics. A Content Analysis looks at four broad categories, 14 specific categories, and 90 topics. The study covers the people behind the Sage LinkedIn postings; purpose of the postings; Sage corporate morals, ethics, social responsibilities, values, and philosophy; Sage today and prospects for the future. The company emits a sense that Sage is a good company to work for, and with, because it cares about the personal concerns and well being of society, regardless of whether businesses or individuals are customers or not. An extensive literature review, including citations, and miscellaneous publications are presented.